2019
DOI: 10.1080/07853890.2019.1693056
|View full text |Cite
|
Sign up to set email alerts
|

Impaired albumin function: a novel potential indicator for liver function damage?

Abstract: Albumin is the most abundant plasma protein and albumin infusion is commonly used. Conventionally, the biologic and therapeutic effects of albumin have been thought to be due to its oncotic properties. However, albumin has a variety of biologic functions, including molecular transport, anti-oxidation, anti-inflammation, endothelial stabilisation, anti-thrombotic effects, and the adjustment of capillary permeability. Despite this, the functions of albumin have not been thoroughly investigated. Recent studies ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 80 publications
(105 reference statements)
0
48
0
Order By: Relevance
“…They also retained the ability to respond to TGF-β1 (1 ng/mL) stimulation, as shown by the decrease in albumin expression and the increase in the expression of α-SMA, that correspond to hepatocellular injury and HSC activation, respectively. Both are known events that occur during liver fibrosis progression [ 29 , 30 , 31 ]. In contrast, dissociation of MTs with Accutase and Accumax led to a lower number of functional HepaRGs, as indicated by the lower number of albumin positive cells following day 3 dissociation ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…They also retained the ability to respond to TGF-β1 (1 ng/mL) stimulation, as shown by the decrease in albumin expression and the increase in the expression of α-SMA, that correspond to hepatocellular injury and HSC activation, respectively. Both are known events that occur during liver fibrosis progression [ 29 , 30 , 31 ]. In contrast, dissociation of MTs with Accutase and Accumax led to a lower number of functional HepaRGs, as indicated by the lower number of albumin positive cells following day 3 dissociation ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of other studies, it has been shown that there is a lag in the increase of liver enzymes after liver function injury. Albumin dysfunction can be adopted as a new potential indicator of liver function injury (39). (2) We should look for malabsorption problems such as eating disorders or celiac disease to improve the nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…More so, albumin is a well-known blood protein transporter and has recently been projected as a key biomarker in clinical diagnosis of early liver impairment. Its decrease in the serum has been implicated in the prognosis of chronic liver diseases such as cirrhosis of the liver, hepatitis and non-fatty acid liver disease (NAFLD) [ 51 ]. Bilirubin is an important molecule with multiple biological functions.…”
Section: Discussionmentioning
confidence: 99%